2000
DOI: 10.1007/s11663-000-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of a CaO-MgO-Al2O3-SiO2 melt containing spinel particles at 1646K

Abstract: This article reports an experimental investigation into the effect of solid suspension on the viscosity of molten slags. Up to about 20 vol pct of spinel (MgAl 2 O 4 ) particles of three size ranges (fine: 0.10 to 0.21 mm; medium: 0.21 to 0.44 mm; and coarse: 0.44 to 0.99 mm) were added to a CaO-MgOAl 2 O 3 -SiO 2 melt at 1646 (Ϯ10) K. A Brookfield DVIIϩ viscometer was used. The viscosity determined for the solid-free melts was in good agreement with the results of published work. The viscosity for the solid-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 8 publications
8
85
2
1
Order By: Relevance
“…In the case of the analysed slag solid elements have a totally different shape and size. These observations are in line with those presented by the authors [9], who drew conclusions concerning the application of Einstein-Roscoe model in determining the dynamic viscosity coefficient of liquid slag systems. Table 4 presents the measurement schemes which were conducted for all samples.…”
Section: Results Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of the analysed slag solid elements have a totally different shape and size. These observations are in line with those presented by the authors [9], who drew conclusions concerning the application of Einstein-Roscoe model in determining the dynamic viscosity coefficient of liquid slag systems. Table 4 presents the measurement schemes which were conducted for all samples.…”
Section: Results Analysissupporting
confidence: 91%
“…The authors did research into the influence of chemical composition, basicity and temperature on the viscosity. Few research centres [8,9] undertook a complicated subject and analysed the changes in the dynamic viscosity coefficient to provide a rheological description of liquid and solid-liquid multicomponent slag systems.…”
Section: Introductionmentioning
confidence: 99%
“…The specific dimensions are listed in Table 2. It should be noted that the actual dimensions of these parts can change at elevated temperatures due to the thermal expansion of the materials, but the dimensional change was assumed to be negligible similar to Wright et al 14) 120 g of the sample was prepared to obtain the mold flux composition listed in Table 1 and placed into the hot zone of the furnace sufficiently purged with 0.4 L/min of Ar. The furnace temperature was calibrated before each experiment using a B-type reference thermocouple inserted from the top of the reaction tube.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…By comparing the measured viscosities with the calculated viscosities by different models, Du et al concluded that Einstein-Roscoe equation was the only model applicably for the systems of Liquid-2CaO.SiO 2 mixtures and liquid-MgO mixtures at the steelmaking temperature, and no modification of the model parameter was found necessary, though the particles were not spherical. 9) However, both Wright et al 7) and Seok et al 8) found that the parameters of Einstein-Roscoe equation should be adjusted to describe the viscosity variation behavior of suspension system.…”
Section: Introductionmentioning
confidence: 99%